The status of Arabian Gazelles Gazella arabica (Mammalia: Cetartiodactyla: Bovidae) in Al Wusta Wildlife Reserve and Ras Ash Shajar Nature Reserve, Oman - Mansoor H. Al Jahdhami; Sultan Al Bulushi; Haitham Al Rawahi; Waheed Al Fazari; Ahmed Al Amri; AbdulRahman Al Owaisi; Salim Al Rubaiey; Zahran Al Abdulasalam; Metab Al Ghafri; Shaeilendra Yadav; Sami Al Rahbi; Steven Ross (Journal of Threatened Taxa, 2017)
We conducted distance sampling surveys of the Arabian Gazelle (Gazella arabica) in two protected areas, Al Wusta Wildife Reserve (WWR) and Ras Ash Shajar Nature Reserve (RSNR), regarded as important for gazelle conservation in northern and central Oman.  The survey in WWR estimated a gazelle density of 0.161 gazelles/km2 in the surveyed area, and in RSNR an estimated density of 25.8 gazelles/km2.  The density of Arabian Gazelle in RSNR is the highest recorded for a wild population.  Using gazelle sighting frequency in non-surveyed parts of each reserve, we estimate Arabian Gazelle populations of 498 and 505 in WWR and RSNR, respectively.  Our surveys demonstrated the potential for a high density of gazelles in well protected and productive habitats, but also that the Arabian Gazelle are in decline in WWR, most likely as a result of poaching and competition with domestic livestock.